Tracing the origins and signatures of selection of antifolate resistance in island populations of Plasmodium falciparum - salgueiro, P.; Vicente, J.L.; Ferreira, C.; Teófilo, V.; Galvão, A.; do Rosário, V.E.; Cravo, P.; João Pinto (BMC Infectious Diseases, 2010)
kground Resistance of the malaria parasite Plasmodium falciparum to sulfadoxine-pyrimethamine (SP) has evolved worldwide. In the archipelago of São Tomé and Principe (STP), West Africa, although SP resistance is highly prevalent the drug is still in use in particular circumstances. To address the evolutionary origins of SP resistance in these islands, we genotyped point mutations at P. falciparum dhfr and dhps genes and analysed microsatellites flanking those genes. Methods Blood samples were collected in July and December 2004 in three localities of São Tomé Island and one in Principe Island. Species-specific nested-PCR was used to identify P. falciparum infected samples. Subsequently, SNPs at the dhfr and dhps genes were identified through PCR-RFLP. Isolates were also analysed for three microsatellite loci flanking the dhfr gene, three loci flanking dhps and four loci located at putative neutral genomic regions. Results An increase of resistance-associated mutations at dhfr and dhps was observed, in particular for the dhfr/dhps quintuple mutant, associated with clinical SP failure. Analysis of flanking microsatellites suggests multiple independent introductions for dhfr and dhps mutant haplotypes, possibly from West Africa. A reduced genetic diversity and increased differentiation at flanking microsatellites when compared to neutral loci is consistent with a selective sweep for resistant alleles at both loci. Conclusions This study provides additional evidence for the crucial role of gene flow and drug selective pressures in the rapid spread of SP resistance in P. falciparum populations, from only a few mutation events giving rise to resistance-associated mutants. It also highlights the importance of human migration in the spread of drug resistant malaria parasites, as the distance between the islands and mainland is not consistent with mosquito-mediated parasite dispersal.